Inspiral : a contrast in operations strategies - Lanza, Alejandro Hernandez de la; Van Mieghem, Jan A. (London : Kellogg School of Management, 2021)
One of the first local manufacturers of screw caps in Chile, INESA expanded rapidly in the region. By 2015, the company had achieved almost 55% market share in the domestic wine sector and 21% in South America, focusing on Chile, Argentina, and Brazil. After more than 40 years in screw cap manufacturing and technical customer support, INESA was acquired in 2017 by RMD Group, which forged a new path to consolidation in the international market.Inspiral was established in 2018 to represent the company's strategy regarding innovation and internationalization. Along with Ramondin (an RMD Group capsule manufacturing brand), Inspiral was a specialist in designing, manufacturing, and packaging a complete portfolio of fastening products for wine, champagne, and spirits bottles.By the end of that first year, two challenges confronted Inspiral: (1) Rapid expansion in the national wine market had seen a similar rising need for quality and low-cost screw caps. As a leading manufacturer of screw caps in Latin America, Inspiral had to create additional value through its strategic positioning and operational excellence. (2) Although Inspiral had the dominant market share, its position was threatened by the possible entry of the Polish company Zakrętka, a major international player, into Chile, Inspiral's home market.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Strategic planning -- Case studies; International business enterprises -- Management -- Case studies